The Challenge of New Forms of Work, Innovative Technologies, and Aging on Decent Work: Opportunities for Occupational Safety and Health - Schulte, Paul; Fischer, Frida Marina; Iavicoli, Ivo; De Anchieta Messias, Iracimara; Fisher, Donald L; Popkin, Stephen M.; Martinez, Maria Carmen; Cotrim, Teresa; Oakman, Jodi (La Medicina del Lavoro, 2024)
Occupational Safety and Health (OSH) can be relevant in achieving the United Nation’s Sustainable Development Goal of decent work by 2030. However, further OSH actions are needed. This paper identifies the role of OSH in addressing two of many determinants of decent work: new forms of work/innovative technologies and worker aging. The authors conducted a discursive analysis of the two determinants and provided examples for consideration. New forms of work/innovative technologies can not only promote but also undermine the future of decent work, and unhealthy aging impedes longer working lives. With a focus on the OSH aspects of new forms of work/innovative technologies and aging, decent work is more likely to be achieved.